"MWPS" -A User Friendly Software for Micro Watershed Characterisation and Prioritization - Ghose, M.K.; Ghosh, S.K.; Srivastava, Y.K.; Chowdary, V.M.; Jeyaram, A. (Journal of Soil and Water Conservation, 2022)
Watershed prioritization involves locating critical areas of erosion, which produce maximum sediment yield to take up conservation activities on priority basis, as such activities cannot be started at the same time in all the watersheds due to various constraints. In the present study, morphometry was the basis for watershed prioritization. Further, the utilitarian aspect of natural resources development within a watershed involving complex computations and decisions are best handled by the modern tools of Geographical Information Systems (CS). In the present study, a GIS customized package has been developed for characterization of drainage and shape parameters of watersheds using ARC/ INFO GIS. The package, MWPS (Micro-Watershed Prioritization Software), is a user-friendly software with Menu/Tool button driven access, which enables the user to calculate the selected attributes from a menu and generate a table containing the attributes of all the micro-watersheds in text format. The algorithm of the software involves computation of morphometric parameters, which are further used for prioritization of watersheds. Computation of morphometric parameters is time consuming and involves laborious mathematical calculations and data manipulation. The MWPS package is of immense help for carrying out the analysis to get accurate results in a time effective manner. Testing and validation of the MWPS package has been carried out by using the micro-watershed and drainage coverage data of Binpur block of Midnapore district of West Bengal.